2013
DOI: 10.1128/jvi.02806-12
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Flavivirus Vaccine by Abolishing Viral RNA 2′- O Methylation

Abstract: Viruses that replicate in the cytoplasm cannot access the host nuclear capping machinery. These viruses have evolved viral methyltransferase(s) to methylate N-7 and 2=-O cap of their RNA; alternatively, they "snatch" host mRNA cap to form the 5= end of viral RNA. The function of 2=-O methylation of viral RNA cap is to mimic cellular mRNA and to evade host innate immune restriction. A cytoplasmic virus defective in 2=-O methylation is replicative, but its viral RNA lacks 2=-O methylation and is recognized and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 34 publications
3
79
0
Order By: Relevance
“…In this work, we focus on the structure/function analysis of ZIKV NS5-MTase, closely related to that of DENV, and involved in the cap structure methylation. The latter is essential for viral RNA translation into proteins and the hiding of viral genomes from detection by cellular antiviral pathways (9,15). The ZIKV MTase presented here crystallizes as a homodimer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we focus on the structure/function analysis of ZIKV NS5-MTase, closely related to that of DENV, and involved in the cap structure methylation. The latter is essential for viral RNA translation into proteins and the hiding of viral genomes from detection by cellular antiviral pathways (9,15). The ZIKV MTase presented here crystallizes as a homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…DENV mutant viruses lacking N-7-methyltransferase (MTase) activity show strong replication defects in infected cells, whereas those altering the 2=-O-MTase activity show only attenuated phenotypes (7,14), as most cell lines used in the laboratory for virus replication are deprived of the RIG-I/MDA5 antiviral pathway. In contrast, it was demonstrated that a 2=-O-MTase knockout virus barely replicates in infected mice and elicits a strong humoral and cellular antiviral response (15,16). Thus, viral RNA capping represents an attractive antiviral strategy (17,18) since it should inhibit viral replication and/or accelerate virus clearance upon stimulation of the innate antiviral response.…”
mentioning
confidence: 99%
“…Virus stocks were stored in aliquots at 280 uC until use. Virus titres were determined by a standard plaque-forming assay in BHK-21 cells (Li et al, 2013a).…”
Section: Methodsmentioning
confidence: 99%
“…Xho I-linearized plasmids were purified and used as DNA templates for in vitro transcription as described previously (Li et al, 2013a) in the presence of an m 7 GpppA cap analogue with a RiboMax Large Scale RNA Production system (Promega). RNA transcripts were transfected into BHK-21 cells with Lipofectamine 2000 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…By inference to the role of capping with mRNA vaccines, the capping of Alphavirus replicons should enhance their applicability without the need for a delivery vehicle. Flaviviruses also require 5'-capping to promote both polyprotein translation and protection of the RNA [42], although an uncapped flavivirus vaccine has been developed [43]. In contrast, application of Pestivirus replicon RNA circumvents the necessity to provide a capping step in the construction and production of the vaccine [40,44], due to the existence of the ribosomal entry site in the 5'-UTR (Figure 2).…”
Section: Important Considerations For Replicon Rna Vaccine Deliverymentioning
confidence: 99%